JAK-STAT and IL-17 pathway dysregulation underlies persistent immune dysfunction in ART-experienced people living with HIV in Ghana - Appeaning, Mark; Magomere, Edwin; Amoako, Nana Ama Yeboaa; Kouffie, Kirk Elorm; Tapela, Kesego; Olwal, Charles Ochieng’; Amponsah, Jones Amo; Nartey, Stella; Baah-Danquah, Rosalynn; Frimpong, Salome Tettey; Quarshie, Seyram Tetteh; Efa-Quayson, Samuel; et al. (Frontiers in Immunology, 2026)
IntroductionChronic immune activation and inflammation are central to HIV pathogenesis and persist despite antiretroviral therapy (ART), contributing to non-AIDS comorbidities. The HIV epidemic in West Africa is distinct, marked by the coexistence of HIV-1, HIV-2 in circulation as well as recombinant forms, yet immune responses in this region remain under-investigated. This study examined how ART modulates cytokine and chemokine signaling in Ghanaian people living with HIV (PLWH), with emphasis on biomarkers of immune dysfunction and treatment response.MethodsPlasma concentrations of 25 cytokines and chemokines were quantified using Luminex multiplex assays in 247 participants: ART-naïve (n=141), post-ART at 6-months (n=52) and 12-months (n=23), ART-experienced (n=74), and HIV-negative controls (n=32). Differentially expressed cytokines, cytokine network analysis, and pathway enrichment analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed using R-anchored packages. Correlations between cytokine levels and viral load were also evaluated. Cox proportional hazards regression was applied to identify biomarker of HIV disease progression and predictive modelling using Least Absolute Shrinkage and Selection Operator (LASSO) regression, Random Forest (RF), and Gradient Boosting Machine (GBM).ResultsART-naïve individuals exhibited elevated pro-inflammatory (IL-6, IL-12/IL-23p40, IL-2, IL-15, IL-2R), and chemotactic (MCP-1, IP-10, MIG) cytokines, alongside reduced IL-1β and IL-1Ra. ART significantly reduced inflammatory cytokines, but paradoxically increased RANTES and Eotaxin. IL-1Ra emerged as the central node in cytokine interaction networks, while IP-10 positively and RANTES negatively correlated with viral load. Lower IL-1β and IL-10 levels predicted virologic control, whereas elevated GM-CSF was linked to persistent viraemia. Machine learning modelling identified RANTES, IP-10, IL-12/IL-23p40, IL-7, and IL-2R as the strongest predictors of viral load. Pathway enrichment analysis revealed upregulation of chemokine-mediated signaling and eosinophil chemotaxis, but downregulation of leukocyte activation, IL-17, and JAK-STAT signaling.ConclusionART attenuates systemic inflammation and partially restores immune balance in PLWH in Ghana, but recovery remains functionally dysregulated, with persistent chemotactic signaling and impaired mucosal and JAK-STAT–mediated immunity. IL-1β, IL-10, GM-CSF, RANTES, and IP-10 emerge as prognostic markers of disease progression and potential targets for adjunctive immunotherapies. These findings underscore the need for immune-modulatory strategies to optimize ART outcomes in West Africa.